Revised Ordinances of the City of Boulder, 157, An Ordinance for the Protection of Several Parks Belonging to the City No. 511 (1899) - (:unkn) unknown (General Publisher, 1899)
Any person other than the police officers of the city who shall take or carry or cause to be taken or carried in to any of the parks belonging to the City of Boulder, any gun, pistol, or revolver, or other firearm, or who shall shoot any firearm at or towards or over or into or upon any of said parks, shall be deemed guilty of a misdemeanor.
--
Keywords: CARRY